Meaning The Mythic Symbols Of Beliefs Of The Sea Island Communities Of South Kalimantan In Film Saranjana: Ghaib City Works Of Johansyah Jumberan - Istianingrum*, Rika; Marsella, Devy; Putri, Wanda; Putri, Ade (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Myths are closely related to local culture in Indonesia. Saranjana City, known as the unseen city, is on Laut Island, South Kalimantan. This city is famous for its myths which are legendary for the people of the region. There are several myths depicted with symbols that can only be understood by the people of the South Kalimantan Sea Island region. The legend of the myth of the city of Saranjana made a film director create it in the form of a feature film in the horror genre. The aim of this research is to describe the meaning of the cultural myth symbols of the people of Laut Island, South Kalimantan in the film Saranjana: Kota Ghaib by Johansyah Jumberan using Roland Barthes' semiotic concept. This research uses qualitative research, with descriptive methods and a phenomenological interpretative approach. The data in this research are symbols in the form of narratives, dialogues, monologues, pictures, scenes from the film Saranjana: Kota Ghaib by Johansyah Jumberan which contains local cultural myths. The results of the research show that there are several myths such as the use of traditional clothes, yellow cloth, mandau and mosquito nets which show symbols believed by the people of Laut Island, South Kalimantan.